The effect of hyperglycemia on the state of muscle tissue in children with type 1 diabetes mellitus - Chudova, N.; Pashkova, O.; Kamenshchyk, A.; Чудова, Наталя Ігорівна; Пашкова, Олена Єгорівна; Каменщик, Андрій Володимирович (My University, 2020)
Introduction: Diabetic myopathy is a clinical condition characterized by decreased muscle mass and skeletal muscle function that has been a little bit studied in children.
Keywords: diabetic myopathy; children; type 1 diabetes mellitus; ultrasound examination